2006
DOI: 10.1016/j.jdeveco.2005.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the minimum wage in Brazil on the distribution of family incomes: 1996–2001

Abstract: The Brazilian economy has long relied on the minimum wage, having first implemented a minimum in 1940. Shortly after taking office in 2003, Brazil's President raised the minimum wage by 20% and promised to double the value of the minimum wage before his term ends in 2006. The usual rationale for minimum wage increases is to bring about beneficial changes in the income distribution, by raising incomes of poor and low-income families. The goal of this paper is to evaluate the efficacy of the minimum wage in Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
3
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 8 publications
3
78
3
10
Order By: Relevance
“…We also found that, on average, workers who lost their jobs in the private covered sector were likely to become unpaid family workers or leave the labor force, and thus earn no income. Given the counteracting wage and employment effects, it was surprising that we found that a higher 16 Contrary to our results, Neumark, Cunningham and Siga (2006) find that in Brazil higher minimum wages have a negative impact on the employment of household heads but a small positive impact on the employment and hours worked of non-heads, and Arango and Panchón (2004) find that in Colombia negative employment effects are larger for household heads compared to non-heards. 17 Note that for non-heads the marginal effect of higher minimum wages on the probability of moving from the private covered sector to self employment is negative and significant, indicating that a higher minimum wage reduces the probability that a non-head will move from the private covered sector into selfemployment.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…We also found that, on average, workers who lost their jobs in the private covered sector were likely to become unpaid family workers or leave the labor force, and thus earn no income. Given the counteracting wage and employment effects, it was surprising that we found that a higher 16 Contrary to our results, Neumark, Cunningham and Siga (2006) find that in Brazil higher minimum wages have a negative impact on the employment of household heads but a small positive impact on the employment and hours worked of non-heads, and Arango and Panchón (2004) find that in Colombia negative employment effects are larger for household heads compared to non-heards. 17 Note that for non-heads the marginal effect of higher minimum wages on the probability of moving from the private covered sector to self employment is negative and significant, indicating that a higher minimum wage reduces the probability that a non-head will move from the private covered sector into selfemployment.…”
contrasting
confidence: 99%
“…Second, we estimate the impact of minimum wages separately on new hires vs. layoffs. Ours is the first study of a developing economy to explicitly show that minimum wages not only result in workers leaving the covered 1 These studies include: Brazil (Lemos, 2009;Neumark, Cunningham and Siga, 2006;Carneiro and Corseuil, 2001;Fajnzylber, 2001), Chile (Montenegro and Pages, 2004); Colombia (Maloney andNunez, 2004, Arango andPanchon, 2004), Costa Rica Terrell, 2005 and2007); Honduras Terrell, 2009 and, Indonesia (Rama, 2001), Kenya (Andalon and Pages, 2008), Mexico (Bosch and Manacorda, 2010;Cunningham and Siga, 2006); Turkey (Ozturk, 2006),Trinidad and Tobago (Strobl and Walsh , 2001), and South Africa (Hertz, 2005). 2 These include studies of the impact of minimum wages in developing economies on: wages and the distribution of wages (Andalon and Pages, 2008;Bosch and Manacorda, 2009;Cunningham, 2007;Hertz, 2005;Lemos, 2009;Maloney and Nunez, 2004;Neumark, Cunningham andSiga, 2006, Stroble andWalsch, 2001;Fanzylber, 2001), employment, unemployment and hours worked (Carneiro and Corseuil, 2001;Terrell, 2007 and2009;Hertz, 2005;Lemos, 2009;Maloney and Nunez, 2004;Montenegro and Pages, 2004;Ozturk, 2006;Rama, 2001), part-time and full-time work …”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, higher minimum wages also reduced the employment of household heads and increased labor force participation slightly for other household members [9]. As noted, higher minimum wages in Colombia and Brazil had a modest impact on poverty and no impact on the incomes of the poorest households.…”
Section: Impacts May Differ Between Household Membersmentioning
confidence: 85%
“…• Likewise, in Brazil, higher minimum wages did not raise the incomes of households in the bottom three deciles of the household income distribution [9].…”
Section: Do Workers Affected By Minimum Wages Live In Poor Households?mentioning
confidence: 92%
“…Örneğin Lemos (2004), Brezilya için yaptığı zaman serileri analizinde asgari ücretin istihdam üzerindeki etkisinin bölgelere ve farklı ücret düzeylerine göre işaret ve anlamlılık seviyelerinde çeşitlilik gösterdiği sonucuna varmıştır [18]. Neumark ve diğerleri (2006) ise Brezilya için hanehalkı düzeyinde yaptıkları zaman serisi analizlerinde asgari ücret artışlarının aile reisi istihdamı üzerinde negatif, diğer hanehalkı üyeleri içinse pozitif ve anlamlı sonuçlar doğurduğuna dair bulgulara ulaşmıştır [19]. Montenegro ve Pages (2004), Çin için yaptıkları [20]' deki panel veri analizinde, asgari ücretteki artışın genç nüfus ve niteliksiz işçi istihdamını azalttığı; fakat kadın istihdamını arttırdığı sonuçlarına ulaşmışlardır.…”
Section: Deneysel çAlışmaların İncelenmesiunclassified